Advance Directives and Personal Identity: What Is the Problem? - Furberg, Elisabeth (Journal of Medicine & Philosophy, 2012)
The personal identity problem expresses the worry that due to disrupted psychological continuity, one person’s advance directive could be used to determine the care of a different person. Even ethicists, who strongly question the possibility of the scenario depicted by the proponents of the personal identity problem, often consider it to be a very potent objection to the use of advance directives. Aiming to question this assumption, I, in this paper, discuss the personal identity problem’s relevance to the moral force of advance directives. By putting the personal identity argument in relation to two different normative frameworks, I aim to show that whether or not the personal identity problem is relevant to the moral force of advance directives, and further, in what way it is relevant, depends entirely on what normative reasons we have for respecting advance directives in the first place.